2020
DOI: 10.1115/1.4046938
|View full text |Cite
|
Sign up to set email alerts
|

A Gaussian Process-Based Crack Pattern Modeling Approach for Battery Anode Materials Design

Abstract: Silicon-based anodes are one of the promising candidates for the next generation high-power/energy density lithium ion batteries (LIBs). However, a major drawback limiting the practical application of the Si anode is that Si experiences a significant volume change during lithiation/delithiation, which induces high stresses causing degradation and pulverization of the anode. This study focuses on crack initiation within a Si anode during the delithiation process. A multi-physics-based finite element (FE) model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In (Li et al, 2019b) (Jain et al, 2014). Moreover, the Gaussian process is also applied to assist in constructing crack pattern model for LIB with silicon-based anode (Zheng et al, 2020), to assist the design of anode material. Specifically, the data points generated by FEM are applied to train their GP-based surrogate model.…”
Section: Battery Modeling and Behavior Predictionmentioning
confidence: 99%
“…In (Li et al, 2019b) (Jain et al, 2014). Moreover, the Gaussian process is also applied to assist in constructing crack pattern model for LIB with silicon-based anode (Zheng et al, 2020), to assist the design of anode material. Specifically, the data points generated by FEM are applied to train their GP-based surrogate model.…”
Section: Battery Modeling and Behavior Predictionmentioning
confidence: 99%
“…Zheng et al. [ 149 ] developed a surrogate GPR model trained to reproduce the results of multi‐physics FE simulations of electrochemical and crack generation processes during anode delithiation. The data for training were generated using an adaptive sampling procedure.…”
Section: Battery Informaticsmentioning
confidence: 99%
“…The crack formation resulting from a significant volume change during anode delithiation is known to be a major limitation of the use of silicon anodes in Li-ion batteries. Zheng et al [149] developed a surrogate GPR model trained to reproduce the results of multi-physics FE simulations of electrochemical and crack generation processes during anode delithiation. The data for training were generated using an adaptive sampling procedure.…”
Section: Battery Modeling and Optimizationmentioning
confidence: 99%
“…In the previous study, we have developed a GP based surrogate model to assist the exploration of the crack initiation phenomenon in the Si anode over the design space. 40 It is found that the GP model can efficiently predict the formation of the lithiationinduced cracks in the Si layer without losing fidelity.…”
mentioning
confidence: 99%
“…Numerical simulation models like FE analysis have been widely adopted in the LIB research field, [31][32][33][34][35][36][37][38][39][40] which are built upon specific physics of failure and can be used to investigate the electrochemicalthermal and electrochemical-mechanical couplings, as well as the capacity degradation failure mechanisms, etc. These models can precisely estimate the electrochemical reactions, Li diffusion, thermal response, and cycle dependent structural changes and stresses and provide valuable insights in understanding the characterizations of sophisticated electrode microstructures, which might be otherwise difficult to study experimentally.…”
mentioning
confidence: 99%